Description of two new species of Calodromus Guérin-Méneville, 1832 from Peninsular Malaysia (Coleoptera: Brentidae, Cyphagoginae) - Cheong, Loong Fah; Bartolozzi, Luca (Fragmenta entomologica, 2018)
Calodromus mantillerii n. sp. and Calodromus goosseni n. sp. from Perak (Malaysia) are described on two single male specimens. The new taxa are closely related to Calodromus insignis (Senna, 1895) but can be easily distinguished by the very different shape of the first tarsal article of the male hind legs. A key for the identification of the males of the three known species of the Calodromus insignis group is provided. A new locality record of Calodromus insignis from Malaysia is also given.